Development of a process control strategy for the serum-free microcarrier expansion of human mesenchymal stem cells towards cost-effective and commercially viable manufacturing - Thomas R.J. Heathman; Alvin W. Nienow; Qasim A. Rafiq; Karen Coopman; Bo Kara; Christopher J. Hewitt (2018)
Human Mesenchymal Stem Cells (hMSCs) are advancing through clinical development with the first allogeneic adult hMSC therapy receiving approval in Europe. To enable successful large-scale manufacture of hMSC therapies, increased product consistency and yield, and a reduced batch-to-batch variation must be achieved. This paper addresses ways to reduce variation by controlling the processing conditions, in particular the dissolved oxygen concentration (dO2), and the culture medium. Bone marrow derived hMSCs were cultured in DASGIP DASbox bioreactors on Plastic P-102L microcarriers in FBS-containing and serum free (SFM) media at various dO2 values from 100% to 10%, experiencing the same dO2 value throughout the culture process. The superior control of pH and dO2 in the bioreactor led to improved performances compared to poorly controlled spinner flasks, particularly at reduced dO2 concentrations. At 25% dO2, there was a 300% increase in the BM-hMSC yield in the bioreactor across the two donor BM-hMSCs in SFM compared to FBS-containing medium. Overall, the process yield increased by an average of around 500% for both donors under controlled conditions in SFM at 25% dO2 in the bioreactor compared to the poorly controlled expansion at atmospheric conditions in FBS-containing medium in spinner flasks. Process control significantly reduced the BM-hMSC variation in yield from 79.1% in FBS-containing medium in spinner flasks to